1997
DOI: 10.1046/j.1464-410x.1997.26714.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant androgen deprivation therapy before radical prostatectomy: who is unlikely to benefit?

Abstract: Objective To determine which patients undergoing radical prostatectomy for localized cancer are unlikely to benefit from neoadjuvant androgen withdrawal therapy. Patients and methods Over a 5‐year period, 173 patients underwent radical retropubic prostatectomy; 87 patients received no pre‐operative androgen withdrawal therapy, for whom the clinical stages were T1b (17 patients), T1c (3), T2a (31) and T2b/c (36). Pre‐operative prostate biopsies contained well‐differentiated cancer in 43 and moderately different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Currently, the rates of pathologically organ‐confined disease are high in some subsets of patients (e.g. low‐stage, low‐grade and low PSA) so that NHT is unlikely to have great additional benefit [ 74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the rates of pathologically organ‐confined disease are high in some subsets of patients (e.g. low‐stage, low‐grade and low PSA) so that NHT is unlikely to have great additional benefit [ 74].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these different modes and duration of hormonal therapy, the studies reported decreased prostate volumes and significant decreases in serum PSA levels after several months of NHT [ 57, 62, 65]. Decreases were particularly notable in the incidence of positive surgical margins in those patients on NHT than in historical controls, unless the tumour volume was large (stage T3) [ 57, 65, 74].…”
Section: Neoadjuvant Hormonal Therapy and Radical Prostatectomymentioning
confidence: 99%
“…Unfortunately, with the exception of the pretreatment PSA, the commonly cited predictors of progression are based on pathology findings after surgery; current investigations into novel markers of biological aggressiveness should enable more accurate predictions of prognosis in the near future [5]. Rabbini et al [66]have suggested that patients with clinically localized, well or moderately differentiated cancer and a preoperative PSA <4 ng/ml are not likely to benefit from hormonal therapy before surgery.…”
Section: Selection Of Patients In the Surgical Settingmentioning
confidence: 99%